(untitled) (Web of Teachers: Inderscience Research, 2025)
The article examines the effectiveness of introducing digital laboratories and simulators into the educational process of biologists through the prism of international TIMSS and PISA studies. The key advantages of virtual experimental environments are analyzed, correlations between the intensity of use of digital tools and students’ academic achievements are revealed. Special attention is paid to the adaptation of educational programs to the requirements of modern science and practical recommendations for the integration of digital technologies into biological education.